Growth Pattern of Mystacoleucus marginatus (Valenciennes 1842) in Cimanuk and Cipeles River, West Java - Rendika Kamiswara; Titin Herawati; Ayi Yustiati; Atikah Nurhayati; Wahyuniar Pamungkas; Walim Lili (Universitas Gadjah Mada, 2022)
Cimanuk River is the second longest river in West Java, flowing from Garut to Indramayu. One of the sub-watersheds of the Cimanuk River is the Cipeles River in Sumedang and Majalengka. Genggehek (Mystacoleucus marginatus) is a type of native fish (indigenous) found in these two rivers. The purpose of the study was to determine growth performance including size distribution, growth pattern and condition factors. The research was conducted by conducting a survey in the dry season in September 2020. The method used was the fisheries biology method. Measurement and data analysis were conducted at the Aquatic Resources Laboratory of Padjadjaran University. The number of fish caught was 231 with a length range of 45 mm - 116 mm and a weight range of 1,1 g – 37,4 g. The growth performance of fish living in Cimanuk River was different from that living in Cipeles River. In Cimanuk River had positive allometric with regression equation W = 4.10-6 L3.2171 and W = 6.10-6 L3.1449. Weight growth was faster than length, condition factor was between 1,27 and 1,33. The growth performance of fish growing in the Cipeles River had a negative allometric growth pattern. The length growth was faster than the weight with the regression equation W = 7.10-4 L2.1182 and W = 7.10-5 L 2.7434, R2 = 0.36 and 0.92, condition factor K = 1.01 and 1.35.